STRENGTHENING DISASTER PREPAREDNESS: INSIGHTS FROM RECENT LITERATURE - Thomas Renjith; Dr Williams Anjana; Dr Arya Anupama (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This paper presents a comprehensive review of recent literature on disaster preparedness, encompassing studies focusing on various aspects such as mental health outcomes, nursing education, training programs, and disaster management protocols. This review provides a comprehensive overview of literature about disaster management, encompassing studies from various geographical contexts and focusing on diverse aspects of disaster preparedness, response, and resilience-building efforts. The literature review encompasses research conducted in countries such as Pakistan, Turkey, Malaysia, Iran, and Egypt, offering insights into the challenges and opportunities associated with disaster management practices. Key themes explored in the literature include posttraumatic growth among trauma victims, disaster preparedness among healthcare professionals, disaster nursing education, and the effectiveness of training programs for disaster response. Studies investigating posttraumatic growth highlight the differential impact of man-made and natural disasters on mental health outcomes, underscoring the need for culturally sensitive interventions and support services. Research on disaster preparedness among healthcare professionals emphasizes the importance of comprehensive training programs and educational initiatives to enhance preparedness levels. Innovative approaches such as simulation-based learning and technology-enhanced training methods show promise in improving response capabilities and resilience in disaster situations. The role of disaster nursing education in preparing future nurses for effective disaster response is also examined, with studies advocating for the integration of disaster-related content into nursing curricula. Additionally, evaluations of disaster management protocols underscore the importance of ongoing assessment and refinement of response strategies to address emerging challenges and enhance healthcare system resilience. Overall, this review highlights the critical importance of evidence-based strategies, interdisciplinary collaboration, community engagement, and technology integration in enhancing disaster preparedness, response, and resilience-building efforts.Top of Form